2015
DOI: 10.5415/apallergy.2015.5.2.68
|View full text |Cite
|
Sign up to set email alerts
|

HLA-B*1502 and carbamazepine-induced severe cutaneous adverse drug reactions in Vietnamese

Abstract: BackgroundIn Vietnam, we observed a high incidence of carbamazepine (CBZ)-induced severe cutaneous adverse drug reactions (SCARs)-Stevens-Johnson syndrome (SJS)/toxic epidermal necrolysis (TEN), and drug-induced hypersensitivity rash with eosinophilia and systemic symptoms (DRESS). In other Asian countries, HLA-B*1502 is an established risk factor for SCARs.ObjectiveThe aim of our study was to determine the frequency of HLA-B*1502 in SCARs patients at a large University Medical Center in Hanoi, Vietnam.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
71
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(82 citation statements)
references
References 42 publications
7
71
1
3
Order By: Relevance
“…One of the first studies demonstrating a strong association between a genetic marker, the HLA-B*1502 allele, and carbamazepine-induced SJS-TEN was performed in Han Chinese in 2004 [51] and has been further replicated by other studies performed in the same ethnic group [52,53] and in other Asian populations [54][55][56][57], but not in Japanese [58,59] or Europeans [60,61]. In contrast to the association between the HLA-B*5801 allele and allopurinol-induced SJS-TEN in various populations [41], the association between carbamazepine-induced SJS-TEN and HLA-B*1502 appears to be ethnicity-specific and has led the United States Food and Drug Administration to recommend screening for this allele in patients of Asian descent before initiating carbamazepine [62][63][64].…”
Section: Carbamazepine-induced Sjs-tenmentioning
confidence: 70%
“…One of the first studies demonstrating a strong association between a genetic marker, the HLA-B*1502 allele, and carbamazepine-induced SJS-TEN was performed in Han Chinese in 2004 [51] and has been further replicated by other studies performed in the same ethnic group [52,53] and in other Asian populations [54][55][56][57], but not in Japanese [58,59] or Europeans [60,61]. In contrast to the association between the HLA-B*5801 allele and allopurinol-induced SJS-TEN in various populations [41], the association between carbamazepine-induced SJS-TEN and HLA-B*1502 appears to be ethnicity-specific and has led the United States Food and Drug Administration to recommend screening for this allele in patients of Asian descent before initiating carbamazepine [62][63][64].…”
Section: Carbamazepine-induced Sjs-tenmentioning
confidence: 70%
“…There have been studies reporting an association between HLA alleles and drug allergy, which were primarily related to the alleles of HLA-A and HLA-B (32). HLA-B*1502 were reported to be associated with carbamazepine-induced Stevens-Johnson syndrome in Asian populations (33)(34)(35) and HLA-A*3101 in European, North American, and Mexican mestizo populations (36)(37)(38). HLA-B*5801 were reported to be associated with allopurinol-induced Stevens-Johnson syndrome or drug-induced hypersensitivity syndrome (39,40), and HLA-B*5701 were reported to be associated with abacavir-induced hypersensitivity reaction (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have found an association between the HLA-B*1502 allele and carbamazepine-induced SJS/TEN in Han Chinese [38][39][40][41] and other Asian populations [42][43][44][45]. The strength of such associations has led to the recommendation to screen for this variant in patients with Asian ancestry before starting treatment [46,47].…”
Section: Anticonvulsantsmentioning
confidence: 99%